Malaysia's 2022 social media marketing trends - Omar Ali, Siti Rapidah; Jusoh, Zuraini (Universiti Teknologi MARA, Terengganu, 2022)
We saw the continuous growth of social commerce in 2022, which allowed users of social media to buy things on social media. Brands and marketers will keep using these and integrating social commerce into their sales strategy. Social media sites are anticipated to keep growing in popularity as consumer purchasing destinations in 2023. Social networks are constantly changing to become retail platforms, from shoppable posts to Instagram Storefronts. The following are Malaysia's current trends in digital marketing